Constitutive expression of full-length or partial of SOC1 genes for yield enhancement in tomato - Danial, Gharbia H.; Jaikham, Jirapa; Song, Guo-qing (Frontiers in Plant Science, 2025)
Manipulating the expression of flowering pathway genes holds potential for regulating tomato fruit productivity. SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 (SOC1) is a MADS-box gene that serves as a key integrator in the flowering pathway. In this study, two full-length SOC1 genes cloned from maize (ZmSOC1) and soybean (GmSOC1), along with a partial SOC1 gene from blueberry (VcSOC1K, containing the K-domain), were individually transformed into tomato for constitutive expression. Phenotypically, the expression of VcSOC1K and ZmSOC1, but not GmSOC1, led to early flowering. Most transgenic lines carrying any of the three constructs exhibited a significant increase in fruit number per plant, with gains of 84-161% for ZmSOC1, 72-135% for GmSOC1, and 55-96% for VcSOC1K. Notably, compared to non-transgenic controls, all three constructs enhanced fruit yield per plant to varying degrees, including ZmSOC1 by 81-169%, GmSOC1 by 60-112%, and VcSOC1K by 52-88%, primarily through enhanced branching. At the transcriptomic level, comparative analysis of GmSOC1 revealed the broader impact of the transformed genes. The increased expression of CLF and EZA1 appears to explain the unchanged flowering time of the GmSOC1 transgenic plants, while the repressed expression of DWARF genes likely contributes to enhanced branching. Additionally, numerous genes associated with biotic and abiotic stress tolerance displayed differential expression. These findings demonstrate that constitutive expression of either full-length or partial SOC1 has the potential to enhance tomato fruit production by modulating multiple pathways, at least at the transcript levels.